2017
DOI: 10.5152/dir.2016.15451
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and safety of the “God’s Hand” pneumatic compression device for hemostasis in femoral catheterization

Abstract: M agnetic resonance imaging (MRI) is a widely used diagnostic tool for breast imaging in daily practice, with its high sensitivity to detect primary, recurrent, and residual breast cancer. Breast MRI serves as a reliable problem-solving tool in case of inconclusive mammography and ultrasonography (US) findings. It can be used to monitor the results of neoadjuvant chemotherapy and it may also contribute to preoperative evaluation of known lesions. With increasing use of MRI, number of breast lesions visible onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Kim et al demonstrated that a pneumatic compression device was effective and safe for the hemostasis of femoral catheterization. They observed that 4 h of bed rest was sufficient for hemostasis (28). Ghods et al compared the efficacy of sandbags and air cushions on complications after coronary angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al demonstrated that a pneumatic compression device was effective and safe for the hemostasis of femoral catheterization. They observed that 4 h of bed rest was sufficient for hemostasis (28). Ghods et al compared the efficacy of sandbags and air cushions on complications after coronary angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The principle is similar to the use of mechanical compression devices at femoral artery catheterization sites to replace traditional manual compression, which is associated with personnel demands, fatigue of the operator's hand and arm, and patient discomfort. 4 In the event of bleeding or oozing at home, patients are routinely instructed to use their fingers to apply firm, continuous pressure directly on the wound for 20 minutes. In reality, patients may not be able to maintain adequate pressure because of fatigue and overestimation of the time lapsed.…”
mentioning
confidence: 99%